Determinación de circulación viral mediante serología de artritis – encefalitis caprina (AEC) en cabras de la parroquia Garzareal, cantón Zapotillo, provincia de Loja. - Sanmartin Freire, Brian Anthony (2025)
CAE is a viral disease that affects goats worldwide, reducing productivity in terms of meat and milk, which has an economic impact on small and medium-scale producers. This study was conducted to determine the presence of caprine arthritis encephalitis (CAE) in the Garzareal parish of Zapotillo canton, Loja province. A total of 95 goats from 19 farms were evaluated using indirect ELISA serology to detect antibodies against the CAE virus. Blood samples were collected to obtain serum, and an epidemiological survey was administered to the farm owners to identify possible factors associated with the presence of the disease. The results revealed a seroprevalence of 6.32% (6/95), with affected farms primarily located in the Balsa Real neighborhood. Arthritic and neurological symptoms were significantly associated with the presence of the virus, aligning with the clinical characteristics of CAE. Additionally, poor management practices were identified, such as low frequency of corral disinfection and lack of control over the introduction of animals from other properties, which may contribute to the disease's spread. The absence of cases in the more isolated Corregidor neighborhood suggests that proximity between farms is a significant factor in the virus's transmission. In conclusion, the results of this investigation indicate that the CAE virus is circulating in goat farms in the Garzareal parish, emphasizing the need to improve biosecurity practices to control its spread and minimize its impact on local goat production.